Korelasi Antara Gaya Hidup Aktif dan Prestasi Akademik Mahasiswa Jurusan PJKR Universitas Negeri Makassar - Juhanis, Juhanis; Fatoni, Fatoni; Iskandar, Iskandar; Anwar, Nur Indah Atifah; Abriadi, Abriadi (Prodi Pendidikan Jasmani dan Olahraga, 2025)
This study aims to analyze the relationship between active lifestyle and academic achievement of students majoring in Physical Education, Health, and Recreation at the Faculty of Sport and Health Sciences, Universitas Negeri Makassar. The study used a quantitative approach with a correlational survey method on 120 active students in semester 4 and above. Active lifestyle data were collected using the short version of the International Physical Activity Questionnaire (IPAQ), while academic achievement data were obtained from students' Cumulative Achievement Index (GPA). Statistical analysis was performed using Pearson correlation at a significance level of 0.05. The results showed that most students were in the moderate to high physical activity category, and there was a significant positive relationship between physical activity levels and GPA (r = 0.427; p = 0.000). These findings indicate that active lifestyle contributes to improving the academic achievement of PJKR students. This study emphasizes the importance of integrating physical activity into students' lives as part of academic and professional development in the field of Physics education. Recommendations are addressed to educational institutions to strengthen campus culture that supports active lifestyles in a sustainable manner.